Developing Competencies for International Entrepreneurship: The Role of a Global Mindset - Muzychenko, Olga; Zalan, Tatiana; Wells, Sam (Senate Hall, 2008)
The focus of this paper is on Entrepreneurial Global Mindset, an important cognitive capability and a source of sustainable competitive advantage for an international new venture. Developing a global mindset means acquiring a set of specific competencies. We put forward a definition of entrepreneurial global mindset and a model linking global mindset and its constituents to competencies and effective task performance. Based on the available evidence regarding what constitutes a global mindset in entrepreneurs and which mindset-related competencies are trainable rather than innate, we suggest that some of these competencies can and should be taught as part of the entrepreneurship education curriculum. We propose entrepreneurship education and training strategies geared toward stimulation of international entrepreneurship and increasing the probability of success of international new ventures.
Keywords: global mindset|international entrepreneurship|competence development